Literature Review: Description of the Psychological Impact of Social Support on Gynecological Cancer Patients - Sukyati, Ira (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims : Gynecological cancer is a group of diseases that develop and attack the female reproductive organs. There are many psychological problems due to the disease, such as anxiety, stress, helplessness, so that they need social support. Objective: to analyze the impact of social support for gynecologic cancer patients, Material and Methods: the research used in this literature study was research that included the inclusion criteria that were made and the databases used, namely the wiley online library, EBSCO, Clinical key, and Google Scholar, Proquest. The keywords used were "gynecological cancer”, “ psychological problems” and” social support”. Results : 229 research results have been found. and those that fit the inclusion criteria totaled six articles. The six articles resulted in findings that social support from family, friends and significant others greatly influences the psychosocial impact of patients reducing depression and increasing acceptance of cancer, having good coping mechanisms in dealing with stress, increasing quality of life and reducing anxiety levels, the patient’s fighting spirit in dealing with cancer and increase patient motivation for treatment. One article describes the impact that the absence of support can lead to feelings of loneliness and loss of hope Conclusion: Social support from family, friends and meaningful people is very useful to help the healing process of gynecological cancer patients